The Influence of Brand Awareness on Consumer Loyalty and the Visualization of a Business Analyst Dashboard for Product X in Malang Regency - Kurnia, Ananda Salwaa; Sri Indriani; Reni Rupianti (Teewan Journal Solutions, 2026)
Competition in Indonesia’s herbal medicine industry is becoming increasingly intense, requiring companies to maintain consumer loyalty through strengthening brand awareness. Product X from PT XYZ is one of the leading products dominating the market; however, market dynamics remain a challenge in sustaining consumer loyalty. This study aims to analyze the effect of brand awareness on consumer loyalty in Malang Regency. The research employed a quantitative approach with a survey of 100 respondents who had consumed Product X at least twice. Data were analyzed using simple linear regression with SPSS and further visualized through a business analyst dashboard in Microsoft Power BI to map consumer behavior and preferences. The findings reveal that brand awareness has a positive and significant effect on consumer loyalty. Brand recognition emerged as the most dominant dimension, while repurchase intention was the strongest indicator of consumer loyalty. The dashboard visualization provides strategic insights into their relationship.